Oskrbovalne verige znanja: Smernice za zeleni in digitalni prehod - Obrecht, Matevž; Cvahte Ojsteršek, Tina; Čuček, Mateja; Fale, Martin; Kajba, Milena; Vičič, Polona; Slomšek Šlamberger, Bojana; Pavić, Lazar (University of Maribor Press, 2024)
Knowledge Supply Chains: Enhancing Wisdom of Green and Digital Transition. The scientific monograph presents the latest findings in the fields of sustainable development and digitalization and applies them to the management of logistics and supply chains. The theoretical part of the monograph opens with chapters that elucidate fundamental concepts in sustainable development, such as sustainable development goals, environmental policy, sustainable production and consumption, the sharing economy, the concept of degrowth and the economy of wellbeing. Next, it discusses the most recent trends in sustainability and the integration of digitalization, whereby the focus is on what is trending and what younger generations perceive as opportunities for priority development. The theoretical section concludes with the presentation of competency models for sustainability and digitalization and the introduction of lifelong learning as a tool for a faster acquisition of knowledge in the areas of sustainable development and digitalization. The latter has been proposed in response to the perceived lack of sustainability and digital skills among individuals who completed formal education at a time when sustainability and digitalization were peripheral topics inadequately integrated into education and the priorities of logistics and supply chains. The research part of the monograph begins by examining the incorporation of sustainable development into the existing legislative framework. Following this, the results of the analysis of the integration of sustainable and digital competencies into Slovenian higher education programmes are presented, along with the results of the analysis of their overlap. The key research output is information obtained from the results of a quantitative study identifying the essential knowledge, skills and abilities needed for the successful simultaneous green and digital transition to Society 5.0 in logistics and supply chains. Additionally, the perceived differences between the economic sector, students and academics in key priority areas are explored.